Prospect theory and asset allocation - Ines Fortin; Jaroslava Hlouskova (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2022)
We study the asset allocation of an investor with prospect theory (PT) preferences. First, we solve analytically the two-asset problem of the PT investor for one risk-free and one risky asset and find that loss aversion and the reference return affect differently less ambitious investors and more ambitious investors. Second, we empirically investigate the performance of a PT portfolio when diversifying among a stock market index, a government bond and gold, in Europe and the US. We focus on investors with PT preferences under different scenarios regarding the reference return and the degree of loss aversion and compare their portfolio performance with the performance of investors under CVaR, risk neutral, linear loss averse and in particular mean-variance (MV) preferences. We find that, in the US, PT portfolios significantly outperform (in terms of returns) mean-variance portfolios in the majority of cases. Also with respect to riskadjusted performance, PT investment outperforms MV investment in the US. Similar results, however, can not be observed in Europe. Finally, we analyze asymmetric effects along economic uncertainty and observe that PT investment leads to higher returns than MV investment in times of larger economic uncertainty, especially in the US.
Keywords: D81; G02; G11; G15; 330; prospect theory; loss aversion; portfolio allocation; mean-variance portfolios; investment strategy